2017
DOI: 10.1186/s13014-017-0798-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of renal function following stereotactic body radiotherapy for pancreatic cancer: secondary dosimetric analysis of a prospective clinical trial

Abstract: BackgroundThis is the first known study examining renal function following stereotactic body radiotherapy (SBRT) for pancreatic head adenocarcinoma.MethodsThirty-eight borderline-resectable/unresectable patients, part of an ongoing prospective trial, underwent 3 cycles of gemcitabine/5-fluorouracil followed by SBRT (5 daily fractions of 5/6/7/8 Gy) and concurrent nelfinavir. Thereafter, in resectable cases, surgery was performed within 4–8 weeks. The last available pre-SBRT creatinine was recorded, along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Retrospective studies have reported renal functional compromise after SBRT that was directed to the kidneys and pancreatic tumors, but to our knowledge, this is the first study to address renal function decline after SBRT that targets the adrenal glands. 65 , 66 , 67 , 68 Siva et al analyzed 21 patients with renal cell carcinoma who were treated with SBRT and assessed the eGFR through 51 Cr-EDTA and 99m Tc-DMSA SPECT/CT images. 65 The researchers reported a mean eGFR drop of 3.2 ± 14.5 ml/min/1.73 m 2 at 3 months and identified a dose-response relationship between eGFR change and SBRT doses.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies have reported renal functional compromise after SBRT that was directed to the kidneys and pancreatic tumors, but to our knowledge, this is the first study to address renal function decline after SBRT that targets the adrenal glands. 65 , 66 , 67 , 68 Siva et al analyzed 21 patients with renal cell carcinoma who were treated with SBRT and assessed the eGFR through 51 Cr-EDTA and 99m Tc-DMSA SPECT/CT images. 65 The researchers reported a mean eGFR drop of 3.2 ± 14.5 ml/min/1.73 m 2 at 3 months and identified a dose-response relationship between eGFR change and SBRT doses.…”
Section: Discussionmentioning
confidence: 99%
“…The available renal OAR constraints were largely derived from published experience in children and adults treated using conventionally fractionated radiotherapy. Only recently has renal function data emerged from patients treated using SABR [7,8]. After SABR to primary renal tumors to a dose of 42 Gy in three fractions, each 10 Gy increase in physical dose led to an exponential decline of 25% in glomerular filtration rates (GFR) [7].…”
Section: Introductionmentioning
confidence: 99%
“…After SABR to primary renal tumors to a dose of 42 Gy in three fractions, each 10 Gy increase in physical dose led to an exponential decline of 25% in glomerular filtration rates (GFR) [7]. For pancreatic tumors, the renal volumes receiving 5 Gy during SABR were significantly associated with changes in GFR, a finding related to steep dose fall-offs outside the pancreas [8]. However, SABR delivery during free breathing may lead to less accurate estimates of doses to a mobile OAR.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, neoadjuvant treatment better favors the delivery of stereotactic body radiation therapy (SBRT), also known as stereotactic ablative radiotherapy, which is a highly conformal modality that affords low doses to surrounding organs-at-risk [7][8]. It has the major advantages of avoiding a protracted interval from diagnosis to surgery, along with increased patient convenience and enhanced cost-effectiveness [9].…”
Section: Introductionmentioning
confidence: 99%